Comparative analysis of monozoic fish tapeworms Caryophyllaeus laticeps (Pallas, 1781) and recently described Caryophyllaeus chondrostomi Barčák, Oros, Hanzelová, Scholz, 2017, using microsatellite markers - Bazsalovicsová, Eva; Králová-Hromadová, Ivica; Juhásová, Ludmila; Mikulíček, Peter; Oravcová, Alexandra; Minárik, Gabriel; Štefka, Jan (Parasitology research, 2020)
The monozoic tapeworm Caryophyllaeus laticeps has been characterized by five markedly different morphotypes largely corresponding to different fish hosts. Recently, the most distinct morphotype 4 from the common nase Chondrostoma nasus was studied in more details resulting in description of a new species Caryophyllaeus chondrostomi. The molecular study based on mitochondrial cox1 and ribosomal lsrDNA did not reveal any interspecific differences between C. laticeps and C. chondrostomi and did not provide any molecular support for recognition of these two species. In the current study, six polymorphic microsatellite markers were applied in order to detect molecular differences between the two species and to provide molecular evidence of validity of C. chondrostomi. While all six microsatellite loci were amplified in different geographic populations of C. laticeps, only two of them provided the amplification product in C. chondrostomi. Results on the Bayesian analysis assigned C. chondrostomi and all geographic populations of C. laticeps to distinct clusters. Neither any close relationships among C. laticeps populations nor specific position of C. chondrostomi were revealed. Contrary, the results of the principal coordinate analysis revealed striking genetic separation of C. chondrostomi with no overlaps with any of the C. laticeps population or morphotype. Caryophyllaeus chondrostomi very probably underwent morphological divergence as a result of ongoing speciation, but this process has not yet been accompanied by sufficient genetic divergence. In this particular case, microsatellites were proved to be better molecular discriminative markers than rDNA and mtDNA.
Keywords: Interspecific differences; Animals; ribozomální DNA; DNA, Ribosomal; Cestoda; Caryophyllidea; cestodózy; Cyprinidae; nemoci ryb; Bayesova věta; Fish Diseases; Bayes Theorem; Molecular taxonomy; cyklooxygenasa 1; Microsatellite Repeats; Cestode Infections; Short tandem repeats; zvířata; mikrosatelitní repetice; Cyclooxygenase 1